Liberalise trade in machines - Ajmani, Manmeet Singh; Roy, Devesh; Takeshima, Hiroyuki (Indian Express Group, 2021)
On July 15, the Centre issued a notification moving power tillers (PT) and their components from the “free” to “restricted” category indicating a clear intent to provide protection to the domestic industry. Power tillers, also known as two-wheel tractors (2WTs) are tailor-made for the farming landscape in India, dominated by small and marginal farmers. This move is symptomatic of heterodox opening policies, being open on the export side while being closed on the import side. Such policies have long-term unintended consequences. One example is subpar mechanisation and productivity loss in agriculture. It is no coincidence that in South Asia, probably the most mechanised agriculture is in Bangladesh delivering significant productivity gains.